A Large-Scale Interprofessional Simulation Experience, Module 2: What Happens in Vegas Does Not Stay in Vegas - Jennifer Namba; Karen Macauley; Amy Zheng; Susie Hutchins; Kathleen Sweeney; Peggy Wallace; Karen Garman; Linda Awdishu (Association of American Medical Colleges, 2016)
Abstract Introduction Interprofessional education (IPE) occurs when students of at least two or more professions learn about, from, and with each profession enhancing the delivery of patient care. The Framework for Action on Interprofessional Education and Collaborative Practice published by the World Health Organization calls for schools of health sciences to train students who are ready to enter the workforce as a member of an interprofessional (IP) team. This IP exercise engaged students in teams composed of three health care professions to provide care to a patient transitioning from the ambulatory to the acute care setting. Methods The case of "What Happens in Vegas Does Not Stay in Vegas" involves a common critical medical condition with a common critical medical condition, for which an IP team of students had to: (1) triage in a timely manner, (2) identify the need for transition of care, and (3) effectively communicate during hand-off from an ambulatory to an acute care settings. The level of learners included second-year medical students, third-year pharmacy students, and first- and second-year graduate prelicensure nursing students. Faculty facilitators from participating programs observed the student teams and led debriefing sessions. The scenario from orientation to debriefing took approximately 4 hours. Results In May 2013, we implemented the IPE experience for 285 students and 88 facilitators over 2 half-days. The following year, 293 students and 100 facilitators took part in the experience. In 2015, 294 students and 93 facilitators took part in this exercise. Achievement of the learning objectives was evaluated through student and faculty surveys, which showed overall positive responses (Response rate, 25%; N = 73). Students agreed or strongly agreed that the case: developed their clinical reasoning skills (88%) and their clinical decision-making abilities (77%); allowed them to demonstrate their clinical decision-reasoning skills (71%), reflect on clinical abilities (96%), apply team-based communication training (71%), recognize clinical strengths and weaknesses (88%), and reflect on and discuss performance (95%); and, enabled learning through feedback (81%). Overall, 92% of students felt that the IPE experience was valuable. Discussion The IPE experience resulted in substantial changes in the curriculum for the pharmacy and medical schools. After the first year, the medical students requested additional content knowledge on handoff of critically ill patients. The medical faculty responded by providing additional education on SBAR within the curriculum. The pharmacy faculty added 10 hours of practical training in the preparation of sterile products and five SP simulations to the curriculum. Although this experience was done on a large scale, it can be adjusted for any number of students.